Iranian clinical practice guideline for amyotrophic lateral sclerosis - Boostani, Reza; Olfati, Nahid; Shamshiri, Hosein; Salimi, Zanireh; Fatehi, Farzad; Hedjazi, Seyed Arya; Fakharian, Atefeh; Ghasemi, Majid; Okhovat, Ali Asghar; Basiri, Keivan; Haghi Ashtiani, Bahram; Ansari, Behnaz; et al. (Frontiers in Neurology, 2023)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegeneration involving motor neurons. The 3–5 years that patients have to live is marked by day-to-day loss of motor and sometimes cognitive abilities. Enormous amounts of healthcare services and resources are necessary to support patients and their caregivers during this relatively short but burdensome journey. Organization and management of these resources need to best meet patients' expectations and health system efficiency mandates. This can only occur in the setting of multidisciplinary ALS clinics which are known as the gold standard of ALS care worldwide. To introduce this standard to the care of Iranian ALS patients, which is an inevitable quality milestone, a national ALS clinical practice guideline is the necessary first step. The National ALS guideline will serve as the knowledge base for the development of local clinical pathways to guide patient journeys in multidisciplinary ALS clinics. To this end, we gathered a team of national neuromuscular experts as well as experts in related specialties necessary for delivering multidisciplinary care to ALS patients to develop the Iranian ALS clinical practice guideline. Clinical questions were prepared in the Patient, Intervention, Comparison, and Outcome (PICO) format to serve as a guide for the literature search. Considering the lack of adequate national/local studies at this time, a consensus-based approach was taken to evaluate the quality of the retrieved evidence and summarize recommendations.